Patients’ and clinicians’ perspectives on the primary care consultations for acute respiratory infections during the first wave of the COVID-19 pandemic: an eight-country qualitative study in Europe - Wanat, Marta; Hoste, Melanie Eugenie; Gobat, Nina Helene; Anastasaki, Marilena; Böhmer, Femke; Chlabicz, Slawomir; Colliers, Annelies; Farrell, Karen; Hollerbach, Sophie; Karkana, Maria-Nefeli; Kinsman, John; Lionis, Christos; et al. (BJGP open, 2022)
The impact of the COVID-19 pandemic on patients' and clinicians' perceptions of healthcare-seeking behaviour and delivery of care is unclear. The pandemic accelerated the use of remote care, and understanding its benefits and drawbacks may inform its implementation during current and future healthcare emergencies. To explore patients' and primary care professionals' (PCPs) experiences of primary care delivery in the first wave of the pandemic. Qualitative study using semi-structured interviews in primary care in eight European countries (England, Ireland, Belgium, the Netherlands, Greece, Poland, Sweden, and Germany). A total of 146 interviews were conducted with 80 PCPs and 66 patients consulting for respiratory tract infection (RTI) symptoms, in eight European countries. Data were collected between April and July 2020, and analysed using thematic analysis. It was found that patients accepted telemedicine when PCPs spent time to understand and address their concerns, but a minority preferred in-person consultations. PCPs felt that remote consultations created emotional distance between themselves and patients, and they reported having to manage diverse COVID-19-related medical and social concerns. Remote consultations for RTI symptoms may be acceptable long term if both groups are happy to use this format, but it is important that PCPs take time to address patients' concerns and provide safety-netting advice.